Natural rubber materials. Volume 2, - Thomas, Sabu; Chan, Chin; Pothan, Laly A.; Joy, Jithin; Maria, Hanna (Royal Society of Chemistry, 2013)
The combination of its unique morphology, physical properties, cost effectiveness and environmental friendliness make natural rubber an appealing constituent for many materials and applications. This comprehensive two volume set covers the synthesis, characterization and applications of natural rubber based blends, interpenetrating polymer networks, composites and nanocomposites. Volume 1 covers different types of natural rubber-based blends and IPNs as well as manufacturing methods, thermo mechanical characterization techniques, life cycle analysis and their applications. Volume 2 focuses on natural rubber-based composites and Nanocomposites including the different types of fillers, the filler-matrix reinforcement mechanisms, manufacturing techniques, and applications. This is the first book to consolidate the current state of the art information on natural rubber based materials with contributions from established international experts in the field. The book provides a "one stop" reference resource for professionals, researchers, industrial practitioners, graduate students, and senior undergraduates in the fields of polymer science and engineering, materials science, surface science, bioengineering and chemical engineering.
Keywords: Rubber.; Composite materials.; elektronické knihy; electronic books